Virtual Reality Trimatra and Dwimatra Laboratory Visual Art Materials for Higher Education - Iriaji, Iriaji; Prasetyo, Abdul Rahman; Aruna, Alby; Putri Surya, Eka; Lydia Ade Vega, Brenda; Marcelliantika, Adinda (KnE Social Sciences, 2023)
Dwimatra and trimatra are currently the main material for university fine arts courses. As a partner campus for the MBKM program, it is obligatory to provide compulsory courses in two dimensions and three dimensions. However, this course is prone to learning misconceptions. As a learning process that prioritizes aesthetics, students are not provided an optimal environment in understanding and experiencing aesthetics due to the lack of accessible virtual infrastructure. This research aims to reduce the misconceptions of the learning problem by providing virtual infrastructure for virtual reality laboratories. The research uses the ADDIE Model method (analysis, design, development, implementation, and evaluation) to develop learning empirically, structurally, and holistically. Validation tests were carried out by material and media experts to determine the media validity. The match pair test is used as a data analysis technique to determine the level of learning outcomes in pre-test and post-test. The hypothetical decision-making guideline on the match pair test refers to the significance value (Sig) if Sig. (2 tailed) < 0.05, then H0is rejected and Hais accepted, if Sig. (2-tailed) > 0.05, then H0is accepted and Hais rejected. The practicality test was conducted to determine the level of media practicality that is obtained from R/SM x 100% with the information R (Achievable Value) and SM (Maximum Score). In this regard, the design of virtual reality laboratories for trimatra and dwimatra art materials for higher education can avoid misconceptions about learning with virtual infrastructure technology. Keywords: trimatra, dwimatra, misconceptions, virtual reality